Article Comments: Is This Truly Feedback for Editorial Boards? Views and Experiences of Journalists - Mažylė, Jolanta (Žurnalistikos tyrimai, 2021)
In the modern society, online comments, especially comments on news websites, create a new problem: in theory, they should guarantee the freedom of speech and improve the work of editorial boards of daily newspapers (news websites). Feedback helps the media to better understand readers and their needs. The essence of feedback for the journalist is to obtain additional information in order to expand the topic of the article, to explore new aspects of the researched subject and to react promptly to relevant information received from the audience. Exploratory research was carried out in May 2021 striving to analyse how much actual feedback works when a media outlet publishes reader comments, as well as to examine how media staff evaluate the necessity of commends under articles and their value for direct work. Fifteen professional journalists – who have more than four years of journalistic experience in national, regional and local media – participated in the research. Research participants were asked 9 questions, of which only several were closed-ended, while the rest were open-ended. The survey was thus carried out in person, seeking to ascertain the questions discussed and clarify situations or circumstances. The duration of each interview was 45-80 minutes. Meetings took place with interviewees or they were contacted via Skype and ZOOM platforms. The article discusses research results, provides examples from editorial experience, as well as reveals views of editorial boards and journalists concerning the phenomenon in question and its problematic aspects.